2006
DOI: 10.1007/s00264-005-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of computerised tomography in management of intra-articular fractures of the os calcis

Abstract: This study aimed to look at the role played by the CT scan in decision making in the management of intraarticular fractures of the calcaneum. Twenty-four patients with intra-articular fractures of the calcaneum were included. Their initial radiographs and CT films were blinded and assessed by three independent observers. Based on this they were selected for operative or non-operative management. The actual management was also recorded. The data were then subjected to statistical analysis to look at the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Typical findings of calcaneal malunion are subtalar arthritis due to posterior facet and calcaneocuboid joint incompatibility, heel widening and sub-fibular impingement of the peroneal tendons due to expansion of the lateral calcaneal wall, reduction of ankle dorsiflexion due to decrease in calcaneal height and hindfoot malalignment and varus deformity due to displaced calcaneal tuberosity. 9,24 This study supports the surgical treatment of displaced calcaneal fractures with open reduction and internal fixation.…”
Section: Discussionsupporting
confidence: 71%
“…Typical findings of calcaneal malunion are subtalar arthritis due to posterior facet and calcaneocuboid joint incompatibility, heel widening and sub-fibular impingement of the peroneal tendons due to expansion of the lateral calcaneal wall, reduction of ankle dorsiflexion due to decrease in calcaneal height and hindfoot malalignment and varus deformity due to displaced calcaneal tuberosity. 9,24 This study supports the surgical treatment of displaced calcaneal fractures with open reduction and internal fixation.…”
Section: Discussionsupporting
confidence: 71%
“…Kumar et al reported that CT scans are not compulsory to determine the need for surgery [7]. Broden views in different angles give valuable information regarding the congruency of the posterior facet of the subtalar joint [1].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there is increased understanding of the pathoanatomy of the fracture [5][6][7]. Non operative treatment, while avoiding the wound issues associated with surgery, results in the fracture being not reduced, malaligned and may cause a bad outcome because of peroneal tendon dislocation, subtalar joint dysfunction, and a non anatomic tuberosity causing disrupted foot mechanics.…”
Section: Introductionmentioning
confidence: 98%
“…The determination of the treatment process is linked to the diagnosis and severity of the fracture. In recent years computed tomography (CT) has been used instead of radiographic methods [27][28][29][30][31] . In calcaneal fractures detailed evaluation of pathoanatomy with CT demonstrating the integrity of the joint surfaces and better understanding of the mechanisms of fracture formation have led to progress in classification and treatment.…”
Section: Discussionmentioning
confidence: 99%